New Uses of Melatonin as a Drug; A Review - Pohanka, Miroslav (Current medicinal chemistry, 2022)
Melatonin is a simple compound called N-acetyl-5-methoxy tryptamine and is known as a hormone controlling the circadian rhythm. Melatonin is produced by the human body naturally. The production of melatonin increases in the evening, causing a state of sleep at night and wakefulness during the day. Melatonin interacts with melatonin receptors MT1 and MT2, but it was revealed that melatonin is a strong antioxidant and it also has a role in the regulation of the cell cycle. Melatonin is now used as a medicine to treat some types of sleep disorders. Moreover, recent research suggests that it can also be utilized for other purposes, such as prevention from chemical exposure and treatment of various diseases, including cancer, neurodegenerative disorders, etc. This review summarizes the basic facts and direction of the current research on melatonin. The existing literature was scrutinized for this review.
Keywords: poruchy spánku a bdění; Circadian Rhythm; Sleep; spánek; melatonin; cirkadiánní rytmus; Humans; lidé; Sleep Wake Disorders; Receptors, Melatonin; melatoninové receptory; Melatonin